DETEKSI TEKANAN DARAH DAN STATUS GIZI, SERTA SOSIALISASI APLIKASI KALKULATOR IMT UNTUK PENCEGAHAN PTM - Setyaningrum, Yahmi Ira; Agustin, Aditya Galih (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2024)
Non-Communicable Diseases (NCDs) have a very high prevalence and most do not know they are affected by NCDs. Early detection efforts are needed to identify NCDs that may occur in adolescents. Teenagers are the next generation towards a Golden Indonesia, therefore health education efforts are needed to prevent PTM. The activity aims to detect the presence of PTM and socialize the BMI calculator application. Community service partners are students who attended Edufair at Gor Ken Arok. The methods used are measuring blood pressure, weight and height, and personal health education through leaflets and a BMI calculator application. The results of blood pressure measurements show that the majority of teenagers have normal blood pressure, but there are still teenagers who are hypotensive or hypertensive. The nutritional status of adolescents measured was mostly normal, but they were still found to be undernourished, overweight and obese. Obesity is still quite high at around 12.5%, so education is needed to maintain ideal body weight. Education is carried out by socializing the use of the BMI calculator application, so that teenagers are motivated to maintain an ideal body weight. In conclusion, detecting blood pressure and nutritional status provides knowledge to teenagers, so they are more aware of their health conditions. The hope is that teenagers will always carry out healthy living behavior to prevent PTM.